Analysis of Seepage and Displacement Field Evolutionary Characteristics in Water Inrush Disaster Process of Karst Tunnel. (9th July 2021) - Lai, Yongbiao; Li, Shuo; Guo, Jiaqi; Zhu, Zhengguo; Huang, Xin
Abstract : Water inrush of tunnel is one of the most common geological disasters in the karst strata in China. Aiming at the rock mass with a quasi-masonry structure in the water-resistant strata between karst cavity with high pressure water and tunnel and the shortcomings of theoretical analysis, traditional numerical simulation, and physics model test for describing and reflecting this special structure of rock mass, a Discrete Element Method considering the fluid-solid coupling effect and structural characteristics of rock mass is employed to study the disaster process of water inrush and the evolutionary characteristics of catastrophe information like seepage pressure and displacement under condition of different karst water pressure, tunnel depth, and lateral pressure coefficient. Research results show the following: (1) the seepage pressure and displacement increase with the increase of kart water pressure. The seepage pressure demonstrates a decreasing state from top to bottom in water-resistant strata, and the time of arrival to a stable value for the seepage pressure shows the time effect. (2) The larger the tunnel depth, the greater the coalescence and distribution scope of fracture and the more likely the water inrush to occur in a short time. The stability of water-resistant strata decreases on the whole with the growth of tunnel depth. (3) The increase of lateral pressure coefficient can restrain the fracture development and strengthen stability. The fracture state is significantly influenced by a lateral pressure coefficient. The results of numerical simulation are consistent with those obtained by a model test. Research and analysis based on energy are a promising train of thought for studying the disaster process of water inrush in a karst tunnel.